Analysis of Socio-Economic Influences on Household Waste Management in West Sumatra - Alya Fariani; Abdul Razak; Indang Dewata; Nurhasan Syah (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to determine the effect of education, population, and technology on household waste management decisions. This study used multiple linear regression analysis with data obtained from BPS Susenas 2023 data in the West Sumatra region. The findings of this study revealed that the level of education (junior high school, high school, and university), population, and technology, did not have a significant influence on household waste management decisions. Although some variables such as technology and education level have a positive relationship direction towards waste management, the results are not statistically significant, which means they are not strong enough to influence households' decision to manage waste. These results suggest that households' decision to manage waste does not only depend on education, population, or technology use, but may also be influenced by other factors, such as environmental socialization, local policies, availability of waste management facilities, and ingrained habits.